"Historia Brittonum" - między oralnością a piśmiennością. Preliminaria - Nowak, Ewa (Uniwersytet Wrocławski. Instytut Studiów Klasycznych, Śródziemnomorskich i Orientalnych, 2016)
The following paper considers the oral and literary sources which might have served as a basis for the History of the Britons (Historia Brittonum), putatively attributed to the 9th century Welsh author Nennius. Given the legendary nature of some of the matter included in the History, such as stories from the Arthurian cycle, as well as the compilatory and in some instances self-contradictory character of the text, the work is supposed to be rooted in the tradition of orally transmitted lore. This tradition preserved knowledge of past events through the dark, i.e. illiterate age following the Anglo-Saxon invasion of Britain. On the other hand the literary sources used by the author of the History have been traced and the work seems to be imbued with the style of ancient annalists, notably Saint Jerome. As such Historia Brittonum should be regarded as being fixed on the verge between the age of oral tradition and that of actual written history.
Keywords: oralność; średniowieczna Walia; średniowieczna historiografia; legendy arturiańskie